Estrogen-related receptors and the control of bone cell fate - Carnesecchi, Julie; Vanacker, Jean-Marc (Molecular and cellular endocrinology, 2016)
Bone loss is naturally occurring in aging males and females and exacerbated in the latter after menopause, altogether leading to cumulative skeleton fragility and increased fracture risk. Two types of therapeutic strategies can be envisioned to counteract age- or menopause-associated bone loss, aiming at either reducing bone resorption exerted by osteoclasts or, alternatively, promoting bone formation by osteoblasts. We here summarize data suggesting that inhibition of the Estrogen-Related Receptors α and/or γ could promote bone formation and compensate for bone loss induced by ageing or estrogen-deficiency.
Available online 20 July 2015
Gesehen am 29.04.2020